Effects of the application of project management techniques on health care project success: A study of Badagry General Hospital, Lagos State - Ibrahim Olateju (Economic and Environmental Studies (E&ES), 2017)
The study examines the effects of the application of project management techniques on health care project success, a study of Badagry General Hospital, Lagos State. Survey research design was adopted for this study. Copies of the questionnaire used for the study were administered to 65 health workers using purposive sampling technique while 256 copies of the questionnaire were administered to patients using simple random sampling technique. The questionnaire for this study was validated using content validity and the reliability of the questionnaire was confirmed by determining the Cronbach's Alpha, which was equal to 0.851. The data collected for the study were presented using charts, tables, percentages and frequencies, while the stated hypotheses were analysed with the aid of correlation analysis and regression analysis. The findings revealed that there is a significant high relationship between resource allocation and sustainability in the health system, with a Pearson's Moment correlation coefficient (r = 0.832, p-value < 0.05). It was also discovered that 85% of the variation recorded in improved quality is accounted for or contributed by monitoring services scheduled. (R2 = 0.85, p-value <0.05). Based on these findings, the study therefore recommended that projects set by a healthcare facility's administrative board must be addressed by a project management team. Healthcare managers must also be concerned with the quality of care and patient outcomes, and lastly that there is need for The Health Information Technology for Economic and Clinical Health (HITECH) Act to be put in place to improve Nigerian healthcare patient care and delivery through an unprecedented investment in Health Information Technology.
Keywords: I10; I14; I15; 330; Health Care; Project Management Techniques; Resource Allocation N; Quality Improvement; Monitoring Services